Simplify the following expression to a fraction in its simplest form: [(4x^2 + 6x)/(2x^2 - x -6)] - [(12)/(x^2 - x - 2)]

2(x+3)/(x+1)

Answered by Dylan H. Maths tutor

8280 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Find the an expression for dy/dx of the function y=(4x+1)ln(3x+1) and the gradient at the point x=1.


Solve the inequality |x - 2sqrt(2)| > |x - 4sqrt(2)|.


Given that 2-3i is a root to the equation z^3+pz^2+qz-13p=0, show that p=-2 and q=5.


Integrate x*ln(x)


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences